State-of-the-art multimodal scanning hard X-ray imaging and tomography sheds light at multiple length-scales on biomineralization related processes - Medjoubi, K.; Benzerara, K.; Debrie, J.; Tang, E.; Bazin, D.; Letavernier, E.; Desjardins, K.; Somogyi, A. (Frontiers in Environmental Chemistry, 2024)
Biomineralization is a widespread process among living organisms, playing a significant role in the formation and preservation of geological structures, biogeochemical cycles, regulation of ocean chemistry, and carbon sequestration. Moreover Pathological pathological biomineralization have has a huge impact on human health. The growth of biominerals provides a rich area for research at multiple length-scales, sincescales since they have controlled hierarchical structures from nano-to macroscopic scales. Here, we provide an overview on the potentials of the state-of-the-art scanning hard X-ray imaging and tomography methods developed at the NanoscopiumNANOSCOPIUM beamline at Synchrotron Soleil in such studies. Multimodal scanning imaging provides simultaneous information on the elemental composition by X-ray fluorescence (XRF) spectrometry, on the sample morphology by absorption contrast imaging, on the crystalline structure by X-ray diffraction, and on the luminescence characteristics by X-ray Excited Optical Luminescence. As illustrated through diverse research cases about biomineralization in stromatolites and pathological calcification, such a versatile portfolio of X-ray imaging techniques provides unique complementary information to conventional laboratory techniques on biominerals and the underlying mineral precipitation processes.